English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

3 answers

B is skew-symmettric iff for all i, j, Bij = - Bji.
The diagonal entries are Bii for some i. Since B is skew-symmetric, Bii = -Bii (set j = i in the first equation). But if Bii = -Bii then 2Bii = 0 so Bii = 0. So all the diagonal entries are 0.

2006-12-20 19:36:01 · answer #1 · answered by Scarlet Manuka 7 · 0 1

if B is skew-symmetric
then B= -B^T (the transpose)
so the diagonal entries: bii have to be equal to =- bii:
bii= -bii
2bii =0
=> bii=0 .

2006-12-21 04:36:37 · answer #2 · answered by Anonymous · 0 0

Skew-symmetric means A^T = -A. Try using the transpose operation on ABA^T and see what you get. Hopefully it comes out to -ABA^T. If you show that steps that's good enough for a proof.

2016-05-23 04:03:32 · answer #3 · answered by Anonymous · 0 0

fedest.com, questions and answers